2019
DOI: 10.1002/fes3.177
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of rhizobium‐soybean symbiosis and nitrogen fixation under drought

Abstract: The symbiotic interaction between soybean plants and rhizobacteria can be severely affected by drought, which results in a reduction in symbiotic nitrogen fixation and ultimately decreased yields. The aim of our research was to determine whether symbiotically efficient rhizobia that can better tolerate soil water deficits can improve nodule performance in plants subjected to drought. Firstly, rhizobial strains were selected that exhibited differences in tolerance to salt (NaCl) or water deficit (PEG 6000). Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 66 publications
1
35
0
1
Order By: Relevance
“…Thus, early drought and low temperature are important factors in regard to efficient N fixation and enhancement of soybean productivity traits. Other studies have reported induced nodule senescence, reduced leghemoglobin content, and BNF in leguminous plants grown under drought conditions compared with their counterparts in well-watered soils ( Ruiz-Lozano et al, 2001 ; Márquez-García et al, 2015 ; Kibido et al, 2020 ). As expected, the moisture regime influenced the shoot biomass increase but did not correspond with N uptake, likely as a result of the dilution effect due to the higher dry matter accumulation in the well-watered conditions ( Jarrell and Beverly, 1981 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, early drought and low temperature are important factors in regard to efficient N fixation and enhancement of soybean productivity traits. Other studies have reported induced nodule senescence, reduced leghemoglobin content, and BNF in leguminous plants grown under drought conditions compared with their counterparts in well-watered soils ( Ruiz-Lozano et al, 2001 ; Márquez-García et al, 2015 ; Kibido et al, 2020 ). As expected, the moisture regime influenced the shoot biomass increase but did not correspond with N uptake, likely as a result of the dilution effect due to the higher dry matter accumulation in the well-watered conditions ( Jarrell and Beverly, 1981 ).…”
Section: Discussionmentioning
confidence: 85%
“…The tolerance of rhizobium strains to drought reflects their ability to remain viable in the soil and is linked to the genetic traits that affect BNF, nodulation, survival, growth rate, and specificity with the host plant ( Zaman-Allah et al, 2007 ). Their efficiency in colonizing roots likely contributes to executing beneficial plant growth-promoting activities ( Kibido et al, 2020 ). On the other hand, the ability of the host plant to enhance BNF under drought conditions is linked to its sustained supply of photosynthates to the nodules ( King and Purcell, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…), which is one of the most important oil and protein crops worldwide, has evolved the ability to host N 2 -fixing bacteria (i.e. rhizobia) in specialized organs called root nodules (Kibido et al 2020;Liu et al 2020). Previous studies revealed that up to 90% of the seed nitrogen (N) content may be derived from N 2 fixation (Mastrodomenico and Purcell 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rhizobia-legume interaction also activates defense responses and increases salt tolerance in soybean seedlings ( Qu et al, 2016 ). In addition, under water deficit conditions, inoculation of rhizobia on soybean resulted in an increased number of nodules ( Kibido et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%